Latin American-European Business Cooperation / Proceedings of the Symposium Held in Montreux (Inter-American Development Bank, 1979)
Introduction, Program of the Symposium, Opening Plenary Session, Second Plenary Session, Third Plenary Session, Fourth Plenary Session, Fifth Plenary Session, Closing Plenary Session, Special SeminarsStrategy Work Groups, Participants.